ON THE ROLE AND IMPACT OF ENERGY DRINKS ON THE HEALTH OF CHILDREN AND ADOLESCENTS (REVIEW) - Kasimova Iroda Khusan kizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
The popularity of energy drinks began to grow actively in the early 2000s, and since then they have become an integral part not only of youth culture but also of the daily lives of many people. In recent years, this trend has noticeably intensified, and Uzbekistan has been no exception. The introduction of energy drinks into the diet can lead to numerous health problems, including sleep disturbances, increased anxiety, and even cardiovascular diseases.